The effects of cardiac rehabilitation on haemodynamic parameters measured by impedance cardiography in patients with coronary artery disease - Stojanović, Milovan; Deljanin-Ilić, Marina; Ilić, Stevan; Petrović, Dejan; Ilić, Bojan (Vojnosanitetski pregled, 2022)
Background/Aim. Well-organized cardiovascular rehabilitation (CVR) reduces cardiovascular burden by influencing cardiovascular risk factors, improving the quality of life, and reducing mortality and hospital readmission. However, its effects on hemodynamic status are largely unknown. The aim of our study was to evaluate the influence of a three-week CVR program on hemodynamic status and to investigate if there is a correlation between physical strain tolerance and hemodynamic parameters measured by impedance cardiography (ICG) before and after the CVR program in patients with coronary artery disease (CAD). Methods.  Fifty-two patients attended a three-week CVR program. At the beginning and the end of the rehabilitation program, laboratory tests, exercise stress tests (EST), and ICG measurements were taken. Results. Patients showed better strain tolerance on the second exercise stress test (EST2) by achieving a higher strain level (Z = 2.315; p = 0.021) and a longer duration of the test (Z = 2.305; p = 0.021). There was a strong positive correlation between the level of EST2 and cardiac output (CO) (r = 0.538; p
Keywords: cardiography, impedance; coronary artery disease; myocardial infarction; physical exertion; plethysmography, impedance; rehabilitation